Risk of developing respiratory symptoms in populations living near artisan brick kilns, El Salvador, 2021-2022 - Lea Hernández; Gerardo Rodríguez; Wendy González; Edgar Quinteros (Journal of Air Pollution and Health)
Introduction: There are many artisans brick kilns near the communities in Nejapa city. The reported prevalence of respiratory diseases or symptoms in this city is 7.2%. This study aims to determine the relationship between exposure to smoke generated by artisan brick kilns and the presence of respiratory symptoms in residents ≥18 years of age in a gated community in the Nejapa city. Materials and methods: This is an analytical cross-sectional study that included 46 individuals. Data were collected through an interview form and an observation form. Frequency analysis, association measures, and prevalence ratios were calculated. This study received ethical approval. Results: Twenty-nine individuals reported respiratory symptoms such as sneezing, itching, and nasal congestion. Twenty-eight people reported experiencing respiratory symptoms. The most frequently reported symptoms were sneezing, nasal itching, nasal congestion, and cough. Daily exposure to smoke from the brick kilns doubled the risk of nasal congestion. Living at 61 m or more from the brick kilns increased the risk of nasal congestion by 3.22 times. Living at a distance between 46 and 60 m from the kilns doubled the risk of coughing. Conclusion: There is a relationship between the development of respiratory symptoms and daily exposure to smoke generated by artisan brick kilns. The risk of developing symptoms varies depending on the distance between the individual’s residence and the brick kilns.